2018
DOI: 10.1016/j.oret.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Scattering Particles in Motion: A Novel Feature of OCT Angiography in Exudative Maculopathies

Abstract: Clinical data suggest that SSPiM is a novel imaging feature of retinal vascular diseases that was not appreciated prior to the use of OCTA. We characterized several novel features of SSPiM and demonstrated that at least in some cases it resolves with residual hard exudate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 19 publications
(20 reference statements)
3
45
0
1
Order By: Relevance
“…The greater the ODR of the intraretinal cyst and the greater the number of HRF, the greater the probability of observing SSPiM. The results of this study are very similar to a previous study 14 . The BRB prevents the migration of large molecules, such as serum proteins, under normal conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The greater the ODR of the intraretinal cyst and the greater the number of HRF, the greater the probability of observing SSPiM. The results of this study are very similar to a previous study 14 . The BRB prevents the migration of large molecules, such as serum proteins, under normal conditions.…”
Section: Discussionsupporting
confidence: 89%
“…However, nonvascular decorrelation signals observed on OCTA are not always artifacts. Kashani et al recently reported a novel artifact-like feature called suspended scattering particles in motion (SSPiM) 14 . Supplementary Figure shows examples of SSPiM.…”
mentioning
confidence: 99%
“…Comparisons using the foveal region are more reliable as they are less affected by segmentations' errors in both the SCP and DCP. In line with Kashani et al 12 , we found that the presence of hyperreflective foveal cysts is related to SSPiM, more frequently using PLEX Elite 9000.…”
Section: Discussionsupporting
confidence: 90%
“…This difference could be explained by technical characteristics of the device used for the analysis and by the position of the borders of the enface slabs. As demonstrated by Kashani et al 12 , the signal detected in SSADA and OMAG models, were different and the OMAG showed more internal reflectivity than SSADA models.…”
Section: Discussionmentioning
confidence: 85%
“…However, there are several limitations associated with the existing metrics. First, although significant correlations have been reported between these metrics and DR severity, no methods have specifically reported the performance on DR cases with DME, which is a challenge for automatic programs because DME is observed to have vessel‐like texture caused by the slow fluid movement inside the edema, termed as suspended scattering particles in motion (SSPiM) . When the edema is near the fovea, it is usually missed in FAZ segmentation by conventional thresholding methods based on pixel intensity.…”
Section: Introductionmentioning
confidence: 99%